10.4k views
2 votes
Solve for x
(X+6)^2 = 8x+36

Solve for x (X+6)^2 = 8x+36-example-1

2 Answers

3 votes

Answer: x1=-4,x2=0

Explanation:

x+6^2=8x+36

Expand the expression

x^2+12x+36=8x+36

Cancel equal terms

x^2+12x=8x

Move the variable to the left

x^2+12x-8x=0

Collect like terms

x^2+4x=0

Factor the expression

x x (x+4) = 0

Separate into possible cases

x=0

x+4=0

Solve the equation

x=0

x=-4

The equation has 2 solutions

x1=-4,x2=0

User Ebone
by
4.2k points
2 votes

Answer:

x=0,x=-4

Explanation:

(x+6)(x+6) =8x+36

x^2+12X+36-8X-36=0

X^2+4X=0

x(X+4)=0

You will get x=0 ,x=-4

User JoeJackJessieJames
by
5.3k points